Study of Expansion Chamber Muffler Characteristics using Pink and White Noise Sources - Kale, A.; Surve, F. (Journal of Scientific Research, 2022)
The primary objective of the study is to compare the insertion loss in an expansion chamber muffler using white and pink noise. White noise has equal power per hertz over the entire range of frequencies, while the power per hertz in pink noise decreases with increasing frequency. Nonetheless, as the width of successive octaves increases, pink noise renders equal power per octave. The sound pressure level at the output port of the expansion chamber muffler is recorded using an acoustic analyzer, maintaining a constant input for the corresponding noise source. Radon Soft, V1.21, has been used for white and pink noise. The response of three different mufflers with varying lengths and cross-sections is investigated for insertion loss, bandwidth, and dissipation: M_1 with m = 4.78 (constant length), M_2 with m = 7.27 (variable length), and M_3 with m = 12.14 (variable length). The experimentally obtained insertion loss and the nature of response are compared with the theoretical estimates of transmission loss.